Dampak Persepsi, Pengetahuan Akuntansi Terhadap Penggunaan Informasi Akuntansi Pada Usaha Mikro Kecil Menengah - Putri, Anisa; Citra Putrantri, Ellyn (Program Studi Akuntansi - STIE Kesuma Negara Blitar, 2024)
The Impact Of Perceptions And Accounting Knowledge On The Use Of Accounting Information In Micro, Small And Medium Enterprises (MSMEs). The aim of the research is to determine whether there is an impact of perceptions and accounting knowledge of MSME business actors on the use of accounting information. The research uses quantitative descriptive methods to determine the influence between variables. There were 97 samples used, namely 97 MSMEs in Kepanjenkidul District, Blitar City. The sampling technique uses proportional random sampling. The research results show that partially the perceptions of MSME actors and accounting knowledge have a significant influence on the use of accounting information. This can be interpreted as if the perception of MSME actors and accounting knowledge increases, the use of accounting information will also increase. Based on these results, it is recommended to business actors that accounting knowledge needs to be improved in order to be able to use accounting information so that they can improve the quality of their business results. In addition, future research is expected to develop populations and other variables to obtain more accurate and comprehensive results.